Stimulasi Kognitif Melalui Tak Tebak Gambar Untuk Mencegah Demensia Pada Lansia - Ahmad, Husnul Hatima; Ridha, Nurul; Oktavia, Tasya; Ridwan, Reskyana; Jaya, Nurulhafisah; Ekasari, Putri Kartika; Pratiwi, Adinda Tasya; Jafar, Nuurhidayat; Mariani, St.; Rahim, Suryadi HS (Jurnal Abdimas ITEKES, 2026)
The global demographic transition has resulted in an increasing elderly population and a rising prevalence of dementia, which poses a significant public health challenge. This Community Service Program (CSP) aims to raise awareness and prevent dementia through education and Group Activity Therapy (GAT) based on picture guessing games in RW 002 and RW 003, Tamalanrea Indah Village, Makassar City. The program involved seven elderly participants aged 65–70 years, with interventions including interactive lectures on dementia and cognitive stimulation through group games. The results demonstrated improved understanding among participants of dementia symptoms, risk factors, and healthy lifestyle practices, alongside active participation exceeding 50% during the activities. This program effectively enhanced social engagement and motivation among participants to maintain cognitive function, particularly via stress management, physical activity, and control of hypertension and diabetes as dementia risk factors. In conclusion, a community-based educational and cognitive stimulation approach is effective in preventing dementia and enhancing the quality of life of the elderly.